2000
DOI: 10.1038/sj.bmt.1702379
|View full text |Cite
|
Sign up to set email alerts
|

Acute lymphoblastic leukaemia-type intensive chemotherapy to eliminate minimal residual disease after high-dose melphalan and autologous transplantation in multiple myeloma – a phase I/II feasibility and tolerance study of 17 patients

Abstract: The modern treatment of new patients with myeloma under the age of 75 years is increasingly involving initial courses of infusional chemotherapy with vincristine, an anthracycline and steroids (ie the C-VAMP programme) 1 followed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…26 C-VAMP has not been eliminated, but has been shifted to a later phase of therapy -and is administered as post-transplant consolidation based upon our prior observations of post-transplant intensive chemotherapy. 27 The idea is to see if the faster attainment of CR increases the proportion of patients remaining in remission long-term ('operational cure'). 28 In conclusion, patients with primary refractory myeloma should receive high-dose melphalan and undergo autotransplantation because a substantial proportion of them respond well and obtain survival benefit.…”
Section: Discussionmentioning
confidence: 99%
“…26 C-VAMP has not been eliminated, but has been shifted to a later phase of therapy -and is administered as post-transplant consolidation based upon our prior observations of post-transplant intensive chemotherapy. 27 The idea is to see if the faster attainment of CR increases the proportion of patients remaining in remission long-term ('operational cure'). 28 In conclusion, patients with primary refractory myeloma should receive high-dose melphalan and undergo autotransplantation because a substantial proportion of them respond well and obtain survival benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 20 clinical trials of newly diagnosed myeloma patients with information on MRD and clinical outcomes were identified and assessed for inclusion in this metaanalysis. Upon careful review of the 20 identified studies (12-14, 16, 18, 21, 58-71), four studies were excluded because they reported on ASCT (61-63, 71); seven were excluded because they did not evaluate the association between MRD status and PFS and/or OS (16,21,(64)(65)(66)(67)(68); four were excluded because they analyzed overlapping cohorts of patients (duplicates) (13,14,18,69); and one was excluded because the timing of MRD analysis was not specified (70). Four studies with information on MRD status and HR for PFS were included in the final analysis (12,(58)(59)(60).…”
Section: Mskcc/nci Meta-analysismentioning
confidence: 99%